Visual learning game / Aina Nasuha Bazli - Bazli, Aina Nasuha (2022)
The development of technology is an affection to the educational field. E-Learning Game is one of the approaches that can be used in the teaching and learning process to make it more effective and interesting. Therefore, this paper is demonstrating the development process of multimedia in e-learning game that can be used for teaching and learning Mathematics of Year 6. The purpose of the development of multimedia in the eteach students who are having difficulty in learning Mathematics using ODL approaches. This e-learning game will help those students to improve their capabilities in answering random quizzes in the meantime. Visual Learning Game (VLG) is a mathematic learning game based on a gaming application that has been developed to help learners to improve their Mathematics of Year 6 and increase their potential in mathematics skills. The purpose of this evaluation is to identify the usability and functionality of the game. This chapter is presenting the enhancement made based on the result in the preview questionnaire that has been distributed to the students.